2016 38th Annual International Conference of the IEEE Engineering in Medicine and Biology Society (EMBC) 2016
DOI: 10.1109/embc.2016.7591952
|View full text |Cite
|
Sign up to set email alerts
|

Tracking driver's heart rate by continuous-wave Doppler radar

Abstract: Developing driving safety system with medical assistance devices for preventing accidents has become a major social issue in recent year. These devices have been developed using electrocardiogram (ECG) and photoplethysmogram (PPG) for measuring the heart rate (HR). However, driver should directly contact with the sensor for monitoring the HR. Recently, non-contact system based on continuous-wave Doppler radar has widely studied for monitoring HR. The periodogram by Fast Fourier Transform (FFT) was used for est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 14 publications
0
15
0
Order By: Relevance
“…In addition, they can be used as a home care service for the elderly through continuous monitoring system [10,11]. Furthermore, they can be used for a driver monitoring system for detecting and alerting drowsy driver [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, they can be used as a home care service for the elderly through continuous monitoring system [10,11]. Furthermore, they can be used for a driver monitoring system for detecting and alerting drowsy driver [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…A similiar approach was proposed by Lee and colleagues in 2016 [ 178 ]. Similiar to Vinci’s second scenario, the authors proposed to place a 24 GHz CW sensor in the backrest of the car seat.…”
Section: Radar-based Methodsmentioning
confidence: 99%
“…This means that the interface is characterized by some sort of impedance measurement. In 2016, Lee et al demonstrated that motion artifacts in radar systems can be greatly reduced using multiple signal classification (MUSIC) [ 178 ]. The authors investigated three different driving conditions: halted vehicle, driving at 60 kmh and driving at 80 kmh.…”
Section: Challenges Of In-vehicle Measurementsmentioning
confidence: 99%
“…Many researches have investigated the heartbeat detection via a Doppler sensor to achieve non-contact heartbeat detection without device attachment. Some conventional methods estimate the HR based on frequency analysis by (i) Fast Fourier Transform (FFT) [10][11], (ii) Wavelet Transform (WT) [12][13], (iii) Multiple Signal Classification (MUSIC) [14] [15], and DCT [16]. In contrast, by detecting a heartbeat signal over the signal obtained through the extended signal processing, the conventional methods [17]- [23] estimate the BBI.…”
Section: Related Workmentioning
confidence: 99%